2019
DOI: 10.4236/als.2019.74013
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Improve: Report of a Three-Year Capacity-Building Project Leveraging Professional Development + Coaching to Improve Third-Grade Reading Outcomes

Abstract: This study reports the results of a three-year capacity building effort to improve core reading knowledge and practice in 165 third-grade teachers working in 63 urban schools and its effects on student reading outcomes. Teachers volunteered to participate in one or two years of professional development lasting from 90 to 180 hours. Core reading knowledge among teachers resulted in statically significant growth with generally large effect sizes. Three cohorts of third-grade students taught by participating teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Biancarosa et al (2010), with a hierarchical, crossed-level, value-added-effects model, compared student literacy learning over 3 years, obtained that PD coaching may have significant effects on students' reading. Paige et al (2019) carried out a longitudinal study (PD lasting from 90 to 180 h) and found that with third-grade teachers, there was statistically significant growth in reading knowledge among teachers with generally large effect sizes and also large effects on all student outcomes with gains in year one exceeded in years two and three.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biancarosa et al (2010), with a hierarchical, crossed-level, value-added-effects model, compared student literacy learning over 3 years, obtained that PD coaching may have significant effects on students' reading. Paige et al (2019) carried out a longitudinal study (PD lasting from 90 to 180 h) and found that with third-grade teachers, there was statistically significant growth in reading knowledge among teachers with generally large effect sizes and also large effects on all student outcomes with gains in year one exceeded in years two and three.…”
Section: Discussionmentioning
confidence: 99%
“…Three university professors explained the initial difficulties in the teaching of reading, relating these to the need to promote professional knowledge (Connor, 2016;Didion et al, 2020;Paige et al, 2019). Evidence collected by the NRP (2000) was presented, highlighting the fact that, after 20 years, this had not been put into practice in the classroom.…”
Section: First Contact: Initial Training In the Traditional Conferenc...mentioning
confidence: 99%
See 2 more Smart Citations
“…While the focus of this literature review centers on understanding the characteristics of PD that increase teacher knowledge and practice, the results from several studies suggest that reform-types of PD that include embedded and ongoing learning over time ultimately increase student reading achievement (Ehri & Flugman, 2018;Gupta & Lee, 2020;Paige et al, 2019;Stark et al, 2020;Wasik & Hindman, 2020). Accordingly, it is possible to infer that increased knowledge has a positive impact on effective practice and effective practice has a positive impact on reading achievement.…”
Section: Structures Specific To Effective Elementary Reading Professi...mentioning
confidence: 99%